Entrepreneurship in and around institutional voids: A case study from Bangladesh - Mair, Johanna; Marti, Ignasi (Journal of Business Venturing, 2009)
In many developing countries those living in poverty are unable to participate in markets due to the weakness or complete absence of supportive institutions. This study examines in microcosm such institutional voids and illustrates the activities of an entrepreneurial actor in rural Bangladesh aimed at addressing them. The findings enable us to better understand why institutional voids originate and to unpack institutional processes in a setting characterized by extreme resource constraints and an institutional fabric that is rich but often at odds with market development. We depict the crafting of new institutional arrangements as an ongoing process of bricolage and unveil its political nature as well as its potentially negative consequences.